Domain swapping to generate new antibiotic proteins - Kapp, James (2024)
Protein-based antibiotics represent a potentially rich source of new therapies to treat rising levels of antibiotic resistant infections. The most potent of these antibiotic proteins are composed of multiple domains from different parental proteins, by borrowing and combining domains from different proteins found in nature we can combine their best features to create new potent therapies. In this project, the cell wall targeting domains (CWTDs) R1R2 and SORT, derived from the S. aureus autolysin AtlA and the sortase recognition motif were used to generate several new antibacterial proteins. Fusion proteins of enhanced green fluorescent protein (eGFP) and the CWTDs were generated to compare the binding of the domains to the binding of the CWTD of lysostaphin (lssSH3B), a protein that has been extensively studied in the literature. Experiments were also conducted that demonstrated the influence of wall teichoic acids (WTAs) on the binding of the R1R2 and lssSH3B domains which revealed that significantly increased binding was seen towards S. aureus with lower levels of WTAs. The chimeras’ lssM23-R1R2, LysKCHAP-R1R2 and lssM23-SORT were successfully generated. The activities of these protein were assessed in MIC and turbidity reduction assays as well as at different pH and NaCl concentrations and compared to the activity of lysostaphin. Knowing that WTAs influence the binding of lysostaphin, an investigation of its synergy with WTA inhibiting antibiotics was carried out. Synergy was seen between lysostaphin and WTA targeting antibiotics with lesser, or no synergy seen with other antibiotics. Experiments with lssM23-SORT suggest that small cationic peptide tags may be useful for generating antibiotic proteins to treat infections at lower pH values. The protein lssM23-R1R2 had a MIC that was comparable to some lysins found in the literature suggesting that autolysin domains should not be immediately disregarded when designing chimeras. Additionally, a strong argument for the use of WTA inhibitors alongside lysostaphin is made. This strategy has the potential to significantly improve the activity of lysostaphin and other antibiotic proteins whose binding are influenced by the presence of WTAs.